1987
DOI: 10.1063/1.98167
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopic evidence of silicon related hydrogen complexes in hydrogenated n-type GaAs doped with silicon

Abstract: Infrared absorption spectroscopy has been performed on hydrogenated and deuterated n-type silicon-doped GaAs. It reveals the presence of a sharp vibrational mode at 890 cm−1 in hydrogenated samples and at 637 cm−1 in deuterated ones. These bands are absent in undoped GaAs. Analysis of the isotopic shift frequency reveals that the band is associated with a hydrogen–arsenic bond where arsenic is supposed to sit as a first nearest neighbor of the silicon donor atom giving rise to (SiAs3)As-H complexes. Isochronal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The Si Ga -H complex in GaAs was the first of this type of complexes thoroughly investigated using vibrational spectroscopy [99,100]. On plasma-passivated MOCVD-grown GaAs samples doped with Si Ga (≈3×10 18 cm −3 ), a pair of vibrational absorption lines were measured after hydrogen as well as deuterium passivation.…”
Section: Group IV Donors On Group Iii Sitesmentioning
confidence: 99%
“…The Si Ga -H complex in GaAs was the first of this type of complexes thoroughly investigated using vibrational spectroscopy [99,100]. On plasma-passivated MOCVD-grown GaAs samples doped with Si Ga (≈3×10 18 cm −3 ), a pair of vibrational absorption lines were measured after hydrogen as well as deuterium passivation.…”
Section: Group IV Donors On Group Iii Sitesmentioning
confidence: 99%
“…Experiments have shown that exposure of Si-doped GaAs to RF hydrogen plasma results in neutralization of the Si donors. Infrared spectroscopy data have also given evidence of (SiAs 3 )As-H complexes [23].…”
Section: Hydrogen Effectsmentioning
confidence: 99%
“…The experimental proof of Si-H complexes has been obtained from infrared local vibrational mode absorption (LVM) spectroscopic measurements [5]. Previous hydrogenation studies on indium-doped CZT have also confirmed the formation of donor impurity indium making complexes with atomic hydrogen [6].…”
Section: Introductionmentioning
confidence: 97%